Income Tax on E-Commerce-Based Export Business Actors Received from Other Countries - Sarmini, sarwini; Irawan, Daveyan Athiyyah Bambang; Roro, Fiska Silvia Raden; Indrawati, Indrawati; Wulaningsih, Ririn Widyastuti (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The rapid expansion of cross-border electronic commerce (e-commerce) has generated complex challenges for national tax systems, particularly with respect to the imposition of income tax on digital export activities. Indonesia’s income tax regime applies the worldwide income principle to resident taxpayers; however, its implementation remains largely grounded in traditional concepts of physical presence, which are increasingly incompatible with digital business models. This study aims to analyze the legal implications of income taxation on export activities conducted through cross-border e-commerce platforms and to examine regulatory responses within the Indonesian tax framework. Using a normative legal research method with statutory, conceptual, and comparative approaches, this study finds that although Law Number 7 of 2021 on the Harmonization of Tax Regulations has introduced the concept of significant economic presence, the absence of detailed implementing regulations limits its operational effectiveness. This condition weakens tax administration, increases the risk of tax avoidance, and creates unequal tax treatment between conventional and digital business actors. Accordingly, adaptive and technology-oriented tax regulation aligned with international standards is required to ensure legal certainty, tax equity, and sustainable state revenue.